Police and policing in India : voices of officers - Barua, S. K. (SAGE knowledge. Cases., 2016)
The case provides an opportunity to discuss the state of policing as a service in India. It contains a short review of key reports that have been brought out over the years on reforms needed in policing in India to make police a force that is responsive to the needs of the society.